2021
DOI: 10.3390/app112110274
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Properties and Microstructure of Non-Calcination Rock Powder Brick with Orthogonal Experiments

Abstract: In this paper, the preparation method and reasonable mix ratio of non-calcination brick with rock powder, cement, lime and fly ash ceramsite (FAC) as the raw materials were experimentally evaluated. To better understand the effects of each component on the performance of non-calcination rock powder brick (NCRPB), an orthogonal experimental design was conducted with the water–cement ratio (W/C), rock powder–cement ratio (R/C), lime content (wl) and FAC content (wf) as the main factors, which involved four facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[4,5] Due to the disadvantages of waste bricks, themselves can't be used repeatedly, research has shown that brick powder has a pozzolanic effect and can be used as a partial substitute for cement in construction production, on the one hand, it can solve the problem of cement energy consumption, on the other hand, it also solves the environmental problems of waste bricks. [6,7] Due to the slow pozzolanic effect of brick powder, in the present study, the main focus is on the study of the excitability of brick powder. [8] In general, the appropriate amount of brick powder will not cause harm to the performance of concrete, but the addition of excessive brick powder will affect the performance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Due to the disadvantages of waste bricks, themselves can't be used repeatedly, research has shown that brick powder has a pozzolanic effect and can be used as a partial substitute for cement in construction production, on the one hand, it can solve the problem of cement energy consumption, on the other hand, it also solves the environmental problems of waste bricks. [6,7] Due to the slow pozzolanic effect of brick powder, in the present study, the main focus is on the study of the excitability of brick powder. [8] In general, the appropriate amount of brick powder will not cause harm to the performance of concrete, but the addition of excessive brick powder will affect the performance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the influence of different admixtures on the performance of concrete through single-factor experiments: an orthogonal combination test [13] has been used to analyze the interaction between different factors to determine the basic mix ratio of printed concrete. According to the requirements of the 3D printing process, fiber optimization is conducted, and the mix ratio of fiber-reinforced concrete is determined.…”
Section: Introductionmentioning
confidence: 99%